2000
DOI: 10.1046/j.1462-2920.2000.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Different portions of the maize root system host Burkholderia cepacia populations with different degrees of genetic polymorphism

Abstract: In order to acquire a better understanding of the spatial and temporal variations of genetic diversity of Burkholderia cepacia populations in the rhizosphere of Zea mays, 161 strains were isolated from three portions of the maize root system at different soil depths and at three distinct plant growth stages. The genetic diversity among B. cepacia isolates was analysed by means of the random amplified polymorphic DNA (RAPD) technique. A number of diversity indices (richness, Shannon diversity, evenness and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…So far, the genetic diversity of natural populations of 'B. cepacia' has been investigated only at the complex level [25,27,42] ; as a consequence, nothing is known about the genetic polymorphism of the Bcc species present in natural populations. In this study, all species and genomovars proved to be highly diverse; in fact, the E index based on RAPD types ranged from 0.98 to 1, indicating that almost all isolates were genetically unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the genetic diversity of natural populations of 'B. cepacia' has been investigated only at the complex level [25,27,42] ; as a consequence, nothing is known about the genetic polymorphism of the Bcc species present in natural populations. In this study, all species and genomovars proved to be highly diverse; in fact, the E index based on RAPD types ranged from 0.98 to 1, indicating that almost all isolates were genetically unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that bacteria of the B. cepacia complex (Bcc), which includes nine species or genomovars (26), may be found in soils (including polluted soils), the rhizospheres of crop plants, and water, as well as in various animal species, in humans, and in the hospital environment (13). Studies published in Europe have shown that Bcc bacteria are good colonizers of the maize rhizosphere, and they may represent one of the predominant bacterial groups in maize grown in Italy (10,17,19). In addition, the species B. graminis (48) and B. cepacia genomovar III (2), presently formally classified as B. cenocepacia (46), were shown to be abundant in maize fields analyzed in France.…”
mentioning
confidence: 99%
“…Despite the great agronomic potential of Burkholderia spp., there is general concern about the environment functioning as a source of human-pathogenic organisms, mainly after B. cenocepacia (genomovar III), which is associated with cepacia syndrome in cystic fibrosis patients, was found as a common plant-associated bacterium (3). Although this finding highlighted the importance of assessing the diversity of Burkholderia species in the rhizosphere, most current ecological knowledge is based on B. cepacia populations isolated from the rhizosphere of just one plant species, maize (5,10,13). Recently, the diversity of the Burkholderia community associated with woodland rhizospheres was also assessed (27).…”
mentioning
confidence: 99%